Pengaruh Kepuasan, Motivasi Kerja, Dan Disiplin Terhadap Kinerja Pegawai - Eris Harismasakti; Nardi Nardi (The Asia Pacific Journal Of Management Studies, 2022)
This study aims to determine the effect of satisfaction, work motivation, and discipline on employee performance, both partially and simultaneously.The method used in this research is descriptive analysis with a quantitative approach. The total population in this study were 73 populations and the sampling technique used was saturated sampling technique. Data collection techniques in this study were through the distribution of questionnaires and library data. The data analysis model used in this study includes: normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test. The hypothesis test used in this study includes: multiple linear regression analysis, correlation coefficient, simultaneous correlation, coefficient of determination, t test and f test.Based on the results of the linear regression test with satisfaction with employee performance, a value of 0.559 is obtained, work motivation on employee performance is obtained a value of 0.540 and the discipline variable on employee performance is obtained a value of 0.163. Based on the results of the correlation coefficient test, the value of satisfaction with employee performance is 0.556, the value of work motivation on employee performance is 0.505 and discipline to employee performance is 0.100. Based on the Hajj, the coefficient of determination obtained the Adjusted R Square value of 0.327. Based on the results of the t test that has been carried out, the satisfaction variable has a positive and significant effect on employee performance. The work motivation variable has a positive and significant effect on employee performance and the discipline variable has no positive and insignificant effect on employee performance. In this study, the significant level was taken = 5% or = 0.05, there was an Fcount value of 12.676 and a Ftable value of 2.74. These results show the value of Fcount (12.676) > Ftable (2.74) with a significance value of 0.000 <0.05. This means that together Satisfaction, Work Motivation, and Discipline have a positive and significant effect on employee performance. Based on data analysis, it can be concluded that partial satisfaction has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. While Discipline has no positive and insignificant effect on employee performance. And simultaneously (together) Satisfaction, Work Motivation and Discipline have a positive and significant effect on employee performance.